Technological Strikebreaking: A Case Study of Quebec’s Anti-Scab Legislation - Talarico, Andrea (Relations industrielles / Industrial Relations, 2021)
SummaryThe right to strike has been constitutionally protected in Canada since 2015. In other jurisdictions where the right to strike is explicitly recognized in the constitution, protection against strikebreaking is recognized as part of that right. Only two Canadian provinces restrict the use of replacement workers during a strike or a lockout. Quebec’s Labour Code has provisions that prohibit the use of replacement workers at the employer’s establishment. Quebec arbitrators, courts, and boards have interpreted this ill-defined concept as a strictly physical location of production, while ignoring technological advances that make remote work possible. This paper examines how the restrictive interpretation of establishment allows a form of strikebreaking that the Spanish Constitutional Court has described as “technological strikebreaking” (esquirolaje technologico), while also allowing the use of technology already at the employer’s disposal to circumvent restrictions on replacement workers even when such technology is not routinely used. The impact of technology on strikebreaking is examined through two case studies: the successive lockouts at the Journal de Québec and the Journal de Montréal. In both cases, external contributors provided the newspapers with content electronically, thus allowing uninterrupted publication. Using Katz, Kochan and Colvil’s three-tier model of collective bargaining, this paper looks at how technological strikebreaking disrupts not only the balance of bargaining power but also bargaining strategy, and how, in the case of the Journal de Montréal, it led to devastating bargaining outcomes. Though the lockouts led to a call for legislative reform in 2011, legislative change is not necessary to align existing provisions with the goal of shortening labour disputes.